Stability of Synthetic Piperazines in Human Whole Blood. Issue 2 (24th November 2017) - Lau, Timothy; LeBlanc, Raquel; Botch-Jones, Sabra
Abstract: While circumventing legislative controls, synthetic piperazines are encountered as "legal" alternatives to ecstasy. Unforeseeable challenges may delay quantitative analysis of these compounds in biological fluids. Enzymatic reactions, matrix interferences and limited knowledge of analyte stability further complicate interpretation of calculated concentrations. The objective of this study was to investigate the stability of synthetic piperazines in human blood under various storage conditions over time. All samples were prepared by spiking certified reference standards (Cayman Chemical, MI, U.S.A.) of eight synthetic piperazine into certified drug-free human whole blood (UTAK Laboratories, Inc., CA, U.S.A.) independently at 1000 ng/mL as well as mixtures containing all tested piperazines in this study. Samples were stored at room temperature ( 20°C), 4°C and −20°C for 1, 3, 6, 9 and 12 months in dark sealed containers. Solid phase extraction (SPE) was performed using mixed-mode copolymeric cartridges (Clean Screen®, UCT Inc., PA, U.S.A.). Analytes were assessed on their degrees of degradation using a Shimadzu Ultra-Fast Liquid Chromatograph with SCIEX 4000 Q-Trap Electrospray Ionization Tandem Mass Spectrometer (UFLC-ESI-MS/MS) in positive ionization mode. Of the two categories, benzyl piperazines were more stable than phenyl piperazines under all storage conditions, in which 1-(4-methylbenzyl)-piperazine (MBZP) had more than 70% (769–1, 047 ng/mL) remaining after 12 months. 1-(4-methoxyphenyl)-piperazine (MeOPP) was not detected under room and refrigerated temperatures after 6 months and was the least stable. Matrix interferences and drug–drug interaction were observed. Storing samples at room temperature should be avoided due to detrimental impacts on stability of piperazine compounds. For backlog situations, case samples suspected to contain synthetic piperazines should be kept frozen or refrigerated even for time periods as short as 30 days for optimal result. Phenyl piperazines stored for more than 6 months showed analyte degradation and loss of parent compounds after extended storage regardless of storage conditions.